Multi-View Technique For 3-D Robotic Object Recognition System Using Neuro-Fuzzy Method. - Osman, M. Khusairi; Mashor, Mohd Yusoff; Arshad, Mohd Rizal (2003)
The recognition of objects is one of the most challenging goals in robotic vision system. The problems increase when the process of recognition involves three dimensional (3-D) objects.